SHORT REVIEW ABOUT DIVERSES ANXIOUS MANIFESTATIONS DESCRIBED IN CHILDREN - Pérez San Gregorio, Mari Ángeles; León Marín, María Rosario; Romo Jiménez, María Lucía; Rodríguez Franco, Luis; Blanco Picabia, Alfonso (Anales de Psicología / Annals of Psychology)
The present paper intends to revise different forms of anxiety states in infancy, emphasizing eight types: Episodic anxiety reaction, panic attacks chronic anxiety states, normal separation anxiety, phobias, hypochondriac manifestations, and obsessive-compulsive reactions. At least, we establish some conclusions, that although not definives, it does offer an up to date view of the state of the matter.